Multi-Agent Systems Modeling, Control, Programming, Simulations and Applications - Alkhateeb, Faisal; Al Maghayreh, Eslam; Abu Doush, Iyad (IntechOpen, 2011)
A multi-agent system (MAS) is a system composed of multiple interacting intelligent agents. Multi-agent systems can be used to solve problems which are difficult or impossible for an individual agent or monolithic system to solve. Agent systems are open and extensible systems that allow for the deployment of autonomous and proactive software components. Multi-agent systems have been brought up and used in several application domains.